2019
DOI: 10.3389/fphys.2019.01374
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Improves Fitness in the Fruit Fly, Drosophila melanogaster

Abstract: It is assumed that a properly timed circadian clock enhances fitness, but only few studies have truly demonstrated this in animals. We raised each of the three classical Drosophila period mutants for >50 generations in the laboratory in competition with wildtype flies. The populations were either kept under a conventional 24-h day or under cycles that matched the mutant’s natural cycle, i.e., a 19-h day in the case of pers mutants and a 29-h day for perl mutants. The arrhythmic per0 mutants were grown together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…We initiated the analysis with these non-isogenic flies. To account for genetic background effects, and since chronometabolomic studies are prone to low reproducibility due to physiological and technical variability [ 17 ], we additionally used highly isogenic WT CS and per 01 flies that were mutually backcrossed for 37 ( per 01 ) and 54 (WT CS ) generations [ 21 ] for control experiments regarding metabolites that significantly differed between the non-isogenic genotypes. In the following, the n on-isogenic and i sogenic flies are referred to as n per 01 / n WT CS and i per 01 / i WT CS , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We initiated the analysis with these non-isogenic flies. To account for genetic background effects, and since chronometabolomic studies are prone to low reproducibility due to physiological and technical variability [ 17 ], we additionally used highly isogenic WT CS and per 01 flies that were mutually backcrossed for 37 ( per 01 ) and 54 (WT CS ) generations [ 21 ] for control experiments regarding metabolites that significantly differed between the non-isogenic genotypes. In the following, the n on-isogenic and i sogenic flies are referred to as n per 01 / n WT CS and i per 01 / i WT CS , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Working with Arabidopsis thaliana , Kim et al [ 16 ] revealed that, within an individual plant, early-emerging (older) leaves had shorter circadian periods of core clock oscillator genes than late-emerging (younger) leaves. Other studies showed that—in cyanobacteria, land plants, and insects—organisms gain a fitness advantage when the external light/dark cycle (T-cycle) matches the endogenous period—a phenomenon known as “circadian resonance” [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Desynchronization between external and internal time reduces overall fitness and is linked to several physiological and mental disorders in humans [2][3][4]. It is therefore important to understand the mechanisms underlying clock synchronization with the natural environmental rhythms.…”
Section: Introductionmentioning
confidence: 99%